2015
DOI: 10.1002/ptr.5444
|View full text |Cite
|
Sign up to set email alerts
|

Anti-carious Effects ofGalla chinensis: A Systematic Review

Abstract: As a natural traditional Chinese medicine, Galla chinensis has been widely used since ancient times for its astringency, stypticity, detoxification, and antibacterial activity. Our group has concentrated on the research about its potential of being an applicable anti-caries agent. The crude extract and some other components purified from it show remarkable efficacy on anticaries, and the most likely mechanism is proposed through specific research. For the fact that crude drugs consist of numerous compounds, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
0
24
0
2
Order By: Relevance
“…GCE contains significant quantities of polymeric and monomeric polyphenols (e.g. gallotannin, GA; chemical structures shown in figure 7 demonstrate the unstable, complex structure of the components) [Xie et al, 2005;Zhang et al, 2015]. Currently, the effective or synergistic components in GCE have been challenging to identify.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCE contains significant quantities of polymeric and monomeric polyphenols (e.g. gallotannin, GA; chemical structures shown in figure 7 demonstrate the unstable, complex structure of the components) [Xie et al, 2005;Zhang et al, 2015]. Currently, the effective or synergistic components in GCE have been challenging to identify.…”
Section: Discussionmentioning
confidence: 99%
“…G. chinensis is harvested in autumn and is processed into medicine through cooking and drying after removing the aphid larvae. Previous studies have revealed that G. chinensis is an effective anticaries agent [Zhang et al, 2015] by inhibiting cariogenic bacteria [Huang et al, 2003;Cheng et al, 2011;Yuen et al, 2011] and demineralization, and enhancing remineralization [Liu et al, 2003;Chu et al, 2006Chu et al, , 2007Huang et al, 2010Huang et al, , 2012. The effective components were determined to be crude G. chinensis extract (GCE, rich in polyphenols), its purified extract GCE-B, and the further purified extracts GCE-B1 and GCE-B2, which were characterized as gallic acid (GA) and methyl gallate, respectively [Xie et al, 2005;Kang et al, 2008;Xie et al, 2008].…”
mentioning
confidence: 99%
“…Among the most promising is Galla chinensis, a leaf gall produced by parasitic aphids, which has been found to be effective in inhibiting demineralization, enhancing remineralization, and increasing the efficacy of fluoride [Cheng et al, 2008[Cheng et al, , 2010. The mechanisms are still not fully clear, but it is hypothesized that polyphenols present in G. chinensis interact with and stabilize the organic matrix remnants, thereby blocking the ion diffusion pathways, and slowing demineralization [Huang et al, 2017;Zhang et al, 2015]. G. chinensis remineralization is believed to be mediated through different polyphenol compounds that act as Ca 2+ ion carriers into the lesion body [Cheng et al, 2015].…”
Section: Fluoride Boostersmentioning
confidence: 99%
“…In most cases Thermogravimetric (TG), Differential Scanning Calorimetric (DSC) and Dynamo-mechanical Thermal (DMT) analyses showed that the desirable characteristics of the UV-cured acrylic resin are not substantially altered by the presence of the organic fillers. The release kinetics of polyphenols and flavonoids, determined in water for TP-containing membranes (ETx) and in ethanol/water mixture (7:3 v/v) for TGP-containing ones (EPx), was satisfactory, reaching a plateau after 24 h. Finally, preliminary antibacterial tests against S. epidermidis were performed on the membranes with higher additive amount and gave positive results for ET-type; on the contrary, no inhibitory effect was observed for the tested EP-type membranes.Polymers 2020, 12, 358 2 of 16 propolis was proven to alleviate the toxic effect of bisphenol A and enhance the growth performance and biochemical variables of Nile tilapia [8].Tea Galla chinensis reveals not only anti-oxidant properties but also anti-carious effects [9]. The tea powder was mainly used orally as a solution in the inhibition of enamel demineralization or remineralization of initial dental caries in vivo [10,11].…”
mentioning
confidence: 99%
“…Tea Galla chinensis reveals not only anti-oxidant properties but also anti-carious effects [9]. The tea powder was mainly used orally as a solution in the inhibition of enamel demineralization or remineralization of initial dental caries in vivo [10,11].…”
mentioning
confidence: 99%